Coronal plane and apical vertebral rotation correction of adolescent idiopathic scoliosis with multisegmented hook-rod system--a retrospective review - Kwan, Mun Keong; Chooi, W.K.; Lim, H.H. (Malaysian Medical Association, 2004)
Between April 1998 and December 1999, thirty patients with Idiopathic Scoliosis were operated with Multisegmented Hook-Rod System. These patients were operated at the mean age of 16 years and were followed up for a mean of 22.3 months (range 13-34 months). Seven patients had anterior release to increase the curve flexibility followed by second stage posterior instrumentation on the same day. The average operating time for a posterior instrumentation alone and anterior release combined with posterior instrumentation were 270 minutes and 522 minutes respectively. The average blood loss was 2.2 litres for posterior instrumentation alone and 3.3 litres for single day anterior release and posterior surgery. The mean preoperative Cobb's angle was 70 degrees. The mean immediate postoperative and final follow up Cobb's angles were 38 and 42 degrees, which represented an average coronal plane correction of 46.7 and 40.0 respectively. The mean preoperative apical vertebral rotation was 25 degrees, which improved to 15 degrees after the operation. At final follow up, the mean apical vertebra rotation was 20 degrees, which represented a mean apical vertebral rotation correction of 20. Complications of the procedure included one transient neurological deficit, one infection, one graft site infection and one case of screw cut out. We were able to obtain satisfactory correction of idiopathic scoliosis with the Multisegmented Hook-Rod System.